ASSESSMENT OF THE INFLUENCE OF NEOINDUSTRIALIZATION FACTORS ON THE SUSTAINABLE DEVELOPMENT OF THE RUSSIA AGRICULTURAL SECTOR - Ivan SANDU; Vasily NECHAEV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article examines the factors of neo-industrialization and their impact on the functioning of Russian agriculture. The purpose of the work is to identify the key factors of neo-industrialization and assess their impact on the sustainable development of agriculture. The scale of technological changes has been studied, and a comparative analysis of neo-industrial trends in various sectors of the agro-industrial complex has been carried out. The specifics of neo-industrial processes in livestock farming are characterized in detail. A mathematical model of threefactor linear regression has been developed, characterizing the influence of parameters of technological development of Russian agriculture on changes in gross value added. The results of the empirical analysis allow us to conclude that there is a direct relationship between capital-labor ratio and gross value added, as well as between the number of highly productive workers and gross value added. It has been calculated that the investment component has the greatest influence. Thus, the increase in the share of investments in reconstruction and modernization in fixed capital affects the increase in gross value added by 223.7 billion rubles. The practical value of the results lies in the development of mechanisms to stimulate and support the introduction of innovations in agricultural production in order to accelerate neo-industrialization.